Avaliação setorial da qualidade de vida em Toledo - Pr: uma análise a partir da percepção da população em 2023 - Lotte, Welthon Roberto (2023)
This study investigates the quality of urban life in different sectors of a city, adopting data collection, which took place through questionnaires applied between October 16 and October 31, 2023, covering an extensive geographic area and considering the interconnection between sectors. The structure of the questionnaire, based on theoretical considerations, addressed several dimensions of community well-being. The sectors were divided and the interviews followed a specific sequence. The evaluation methodology included a calculation with three categories, each with variable weight, derived from the answers to the questionnaire. This involved final parameters for infrastructure, proximity, and safety, calculated from averages of final micro-evaluative values. The resulting score was rated on a micro quality scale, ranging from very poor to excellent. Subsequently, the Quality of the Sector (QS) was calculated by adding the averages obtained in each category. This provided an accurate assessment of the quality of the sectors at the individual and aggregate level by comparing the score to a macro quality scale. The spreadsheet used facilitated the compilation and analysis of the data, allowing the categorization of answers and the inclusion of the "I don't know" option. The micro calculation, exemplified in charts 2, 4, 5, 6, 7 and 8, revealed a detailed analysis of the population's perceptions of infrastructure, security and proximity. In summary, a comprehensive and detailed understanding of the quality of urban.